Oxford Textbook of Public Mental Health 2018
DOI: 10.1093/med/9780198792994.003.0051
|View full text |Cite
|
Sign up to set email alerts
|

Non-governmental organizations and mental health

Abstract: This chapter examines to contribution of non-governmental organizations (NGOs) to meeting the mental health needs of individuals, families, and communities. After providing an overview of the history of mental health NGOs, and the current policy frameworks within which they work, it then examines the scope of mental health NGOs, and maps the main international networks and within the UK context. It examines the contribution of NGOs, the key challenges they face working within mental health, and concludes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The concept of mental well-being was developed in the context of positive psychology (Jahoda, 1959), and various studies have shown that good mental health is more than simply the absence of mental illness (Huppert and Whittington, 2003; Keyes, 2015; Shah et al , 2021). Importantly, mental well-being covers both hedonic (feeling good) and eudemonic (functioning well) aspects, with both aspects being integral parts of the overall construct (Regan et al , 2016). Previous research has shown moderate-to-strong negative associations between mental well-being and symptoms of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of mental well-being was developed in the context of positive psychology (Jahoda, 1959), and various studies have shown that good mental health is more than simply the absence of mental illness (Huppert and Whittington, 2003; Keyes, 2015; Shah et al , 2021). Importantly, mental well-being covers both hedonic (feeling good) and eudemonic (functioning well) aspects, with both aspects being integral parts of the overall construct (Regan et al , 2016). Previous research has shown moderate-to-strong negative associations between mental well-being and symptoms of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Carless and Sparkes 2008;Kiddey 2014;McEvoy et al 2012). Contemporary mental health recovery models recognize these factors as positive contributors, advising their implementation into individuals' everyday lives (Jacob 2015;Regan et al 2016.). These therapeutic characteristics are clearly not unique to archaeology.…”
Section: Introductionmentioning
confidence: 99%